Umbilical Cord Stem Cell Lysate: A New Biologic Injectate for the Putative Treatment of Acute Temporomandibular Joint Inflammation - Ward CK; Gill RG; Liddell RS; Davies JE (Journal of Inflammation Research, 2023)
Christopher K Ward,1,* Rita G Gill,2,* Robert S Liddell,2 John E Davies1,2 1Faculty of Dentistry, University of Toronto, Toronto, Ontario, Canada; 2Institute of Biomedical Engineering (BME), University of Toronto, Toronto, Ontario, Canada*These authors contributed equally to this workCorrespondence: John E Davies, Institute of Biomedical Engineering (BME), University of Toronto, 164 College Street, Toronto, Ontario, M5S 3G9, Canada, Tel +1 416 414 0908, Email jed.davies@utoronto.caObjective: To compare in vivo, the acute anti-inflammatory effects of a lysate derived from human umbilical perivascular mesenchymal cells with the cells themselves in both an established hind-paw model of carrageenan-induced inflammation and also in the inflamed temporomandibular joint.Study Design: Human umbilical cord perivascular cells were harvested and cultured in xeno- and serum-free conditions to P3. In addition, P3 cells were used to prepare a proprietary 0.22 micron filtered lysate. First, CD1 immunocompetent mice underwent unilateral hind-paw injections of carrageenan for induction of inflammation, followed immediately by treatment with saline (negative control), 1% cell lysate, or viable cells. The contralateral paw remained un-injected with carrageenan. Paw circumference was measured prior to injections and 48 hr later and myeloperoxidase and TNF-alpha concentrations were measured post-sacrifice in excised tissue. Second, immunocompetent Male Wistar rats underwent unilateral intra-articular temporomandibular (TMJ) injections from the same treatment groups and were sacrificed at 4 and 48 hr post-injection. The contralateral TMJ remained un-injected with carrageenan. Articular tissue and synovial aspirates, from the treated TMJ were obtained for histologic and leukocyte infiltration analyses.Results: The lysate and cell-treated hind-paw demonstrated reduced tissue edema, and significantly lower concentrations of myeloperoxidase and TNF-alpha at 48 hr compared to untreated controls. Treated TMJs demonstrated lower concentrations of leukocytes in the synovium compared to controls and histologic evidence, in the peri-articular tissue, of reduced inflammation.Conclusion: In this preliminary study, both the human umbilical perivascular cells and a highly diluted lysate produced therefrom were anti-inflammatory.Keywords: TMJ-OA, mesenchymal cell, cell lysate, anti-inflammatory, carrageenan model, mouse and rat